Impact evaluation and cost-Benefit analysis of remote orthopedic consultation methods in a low-resource health-care setting - Deeptiman James; Nirmal Kurian; Arun John; Viju Daniel Verghese; Vinoo Mathew Cherian (Wolters Kluwer Medknow Publications, 2021)
Background: Geographic barriers, inadequate infrastructure, and large-scale logistics severely limit telemedicine and e-health systems' ability to make orthopedic care accessible to masses in rural centers. With <1% of the registered hospitals in our country connected through telemedicine, novel alternatives are necessary for effective remote consultation in low-resource health-care settings. Materials and Methods: A retrospective cohort analysis to compare the impact of "e-mail and telephone-" and "WhatsApp-" assisted remote orthopedic consultations (ROCs) on surgical decision-making and outcome of complex orthopedic conditions treated at a remote location hospital in Central India was conducted by assessing the response time, clarity, peer review accessibility, cost-effectiveness and functional outcome parameters (Visual Analog Score [VAS] and Single Assessment Numerical Evaluation [SANE]), complication rates, and duration of hospital stay. Unpaired t-test was used for statistical analysis. Results: Forty-eight patients were included in the study. Remote consultation was carried out through "e-mail and telephone" for 17 patients and through "WhatsApp" for 31 patients. "WhatsApp-" assisted remote consultation enabled quicker response (P < 0.0001), ensured nonambiguity (P < 0.0001), was cost-effective, and facilitated more peer review (P < 0.0001). Mean VAS and SANE scores reflected better outcome in the "WhatsApp-" assisted remote consultation (P < 0.0001), but hospital stay and complication rates were higher in this group. Conclusions: "WhatsApp-" assisted ROC had a higher impact and was cost-effective in management of complex orthopedic conditions in the low-resource setting.